(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
the connection of diseases of the upper and lower respiratory tract is noted in a large number of studies and is explained by various theories. In particular, there is evidence that nasal symptoms in diseases of the nasal cavity and paranasal sinuses affect exacerbations of chronic obstructive pulmonary disease (COPD). Accordingly, therapy aimed at the treatment of rhinosinusitis can alleviate the condition and improve the quality of life of this category of patients. The aim of the study was to evaluate the clinical efficacy, tolerability and safety of a combined drug with antibacterial, anti-inflammatory and vasoconstrictive effects in patients with acute rhinosinusitis (mild and moderate course) and concomitant COPD.